MENINGKATKAN KELINCAHAN DAN KECEPATAN DALAM BERMAIN SEPAK BOLA PADA SISWA KELAS X SMA NEGERI 1 MAMUJU - Rusman Rusman (PINISI :Journal of Teacher Professional, 2021)
Speed and agility are the basic capital in playing football and for players are the main capital for scoring goals, as well as keeping the ball conceded. With the ability to speed will make it easier for players in order to carry the ball. The problems that can be studied in this study are: (a) How to increase the achievement in mastering the basics of football for class X students of SMA Negeri 1 Mamuju, when the demonstration method is applied? (b) How does the demonstration method influence student learning motivation? The aims of this study were (a) to find out the increase in learning achievement of the basics of football in Class X students of SMA Negeri 1 Mamuju after applying the demonstration method, (b) to find out the motivation to learn the basics of football after applying the demonstration method. This study used two rounds of action research. Each round consists of two stages: design, activity and observation. Reflection and revision Research objectives. The subjects of this study were Class X students at SMA Negeri 1 Mamuju, Mamuju Regency. From the data obtained in the form of practical test results, observation sheets of teaching and learning activities From the results of data analysis, it was found that student achievement increased from cycle I to II, namely, cycle I (61.54%), cycle II (89.74%) to the psychomotor domain, cycle I (84.62%). Cycle II (100%) for the affective domain, the demonstration method can have a positive effect on learning motivation in class X students at SMA Negeri 1 Mamuju and the learning model can be used as an alternative to Physical Education and Sports in SMA. Keywords: Learning Achievement, demonstration methods and playing soccer.